1967
DOI: 10.1071/ch9672677
|View full text |Cite
|
Sign up to set email alerts
|

Electron impact studies. XVIII. Mass spectra of pyridazines, phthalazines, and related compounds

Abstract: The mass spectra of substituted pyridazines, phthalazines, and related compounds are reported and discussed. Molecular ions are a prominent feature of all the spectra, and fragmentation modes may be usefully correlated with both the type of heterocycle and its substitution pattern. Fragmentation patterns have been substantiated by extensive high resolution studies and appropriate metastable ions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1973
1973
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…The masses of the pyridazine cations recorded in this region of the mass spectrum denote losses of neutral HCN (m = 27 amu) or N 2 (m = 28 amu) stable molecules by the parent cations, which may be further accompanied by abstraction of H atoms. The 53 and 52 amu peaks match the C 3 H 3 N + and C 4 H + 4 cations formed by the loss of a single HCN or N 2 [13,45] molecules, respectively. However, in the high resolution measurements Benn et al [12] revealed that the 52 amu peak also contains a contribution (26.5% at 70 eV) from the C 3 H 2 N + cations.…”
Section: Cations: M = 49-53 Amumentioning
confidence: 85%
See 1 more Smart Citation
“…The masses of the pyridazine cations recorded in this region of the mass spectrum denote losses of neutral HCN (m = 27 amu) or N 2 (m = 28 amu) stable molecules by the parent cations, which may be further accompanied by abstraction of H atoms. The 53 and 52 amu peaks match the C 3 H 3 N + and C 4 H + 4 cations formed by the loss of a single HCN or N 2 [13,45] molecules, respectively. However, in the high resolution measurements Benn et al [12] revealed that the 52 amu peak also contains a contribution (26.5% at 70 eV) from the C 3 H 2 N + cations.…”
Section: Cations: M = 49-53 Amumentioning
confidence: 85%
“…The mass spectra of gas phase pyridazine have been investigated less frequently than those of pyrimidine. Electron impact induced mass spectra were reported in the mid-1960s and early 1970s [11][12][13][14]. High mass resolution measurements, using double focusing mass spectrometer, have been carried out just in [11], while the other works concentrated principally on the studies of the most abundant cations.…”
Section: Introductionmentioning
confidence: 99%
“…It is produced from b by the elimination of neutral COCH(O)yR and ring contraction, common processes for oxadiazoles 16 and pyridazines. 12 In the saturated compounds (j = 2) the ion m/z 141 arises from structure a which was confirmed by the appropriate metastable transitions in compound 7. In compounds with j = 2, p = 1, y = 1 the ion m/z 127 is formed via routes a and b and are of higher intensity relative to m/z = 125 in the compounds with j = 1, p = 1, y = 1 as can be seen in Figs 3 and 4 respectively.…”
Section: Resultsmentioning
confidence: 82%
“…The elimination of neutral CO is commonly observed for carbonyl compounds. 6,[10][11][12][13][14] The ion b 11 is produced from b after a rearrangement involving the transfer of H from N Á to C (three membered transition state) and of the OR group to the carboxylic group and elimination of the radical COOR. The rearrangement processes with ring contraction 15,16 and group migration [16][17][18][19][20] on compounds containing N and O has been known for some time.…”
Section: Resultsmentioning
confidence: 99%
“…It is produced from b by the elimination of neutral COCH(O)yR and ring contraction, common processes for oxadiazoles 16 and pyridazines. 12 In the saturated compounds (j = 2) the ion m/z 141 arises from structure a which was confirmed by the appropriate metastable transitions in compound 7. In compounds with j = 2, p = 1, y = 1 the ion m/z 127 is formed via routes a and b and are of higher intensity relative to m/z = 125 in the compounds with j = 1, p = 1, y = 1 as can be seen in Figs 3 and 4 respectively.…”
Section: O]mentioning
confidence: 80%